A new insight into the low membrane fouling tendency of liquid-liquid hollow fiber membrane contactor capturing ammonia from human urine. (15th April 2023) - Zhang, Junhui; Li, Kuiling; Xie, Mengfei; Han, Qi; Feng, Li; Qu, Dan; Zhang, Liqiu; Wang, Ke
Highlights: Higher pH achieved excellent NH3 capture property and slight membrane fouling. Energy barrier of foulant-membrane increased with the increasing feed urine pH. Absence of water permeate drag force greatly alleviated membrane fouling. Low attractive force near the membrane further relieved membrane fouling at high pH. Abstract: To unravel the low membrane fouling tendency and underlying membrane fouling mechanism of liquid-liquid hollow fiber membrane contactor (LL-HFMC) capturing ammonia from human urine, the ammonia flux decline trend, membrane fouling propensity, foulant-membrane thermodynamic interaction energy and microscale force analysis at different feed urine pH were comprehensively investigated. The 21-d continuous experiments showed that the ammonia flux decline trend and membrane fouling propensity significantly strengthened with the decrease of feed urine pH. The calculated foulant-membrane thermodynamic interaction energy decreased with the decreasing feed urine pH and agreed with the ammonia flux decline trend and membrane fouling propensity. The microscale force analysis showed that the absence of hydrodynamic water permeate drag force resulted in the foulant located at long distance from the membrane were difficult to approach the membrane surface, thus considerably alleviating membrane fouling. Additionally, the vital thermodynamic attractive force near the membrane surface increased with the decrease of feed urine pH, which made the membrane fouling further relieved at high pH condition. Therefore, the absence of water permeate drag force and operating at high pH condition minimized the membrane fouling during the LL-HFMC ammonia capture process. The obtained results provide a new insight into the low membrane tendency mechanism of LL-HFMC. Graphical abstract: Image, graphical abstract